Exploratory Study of Sensitization in Cryogenically Cooled Ferritic Stainless Steel Welds. (4th December 2014) - Amuda, M. O. H.; Mridha, S.
Abstract : Enhanced cooling via forced convection using cryogenic liquid is an option for controlling grain growth in the heat affected zone (HAZ) of ferritic stainless steel welds which improves joint strength. However, this technique seems to alter the martensite distribution in the high-temperature heat affected zone (HTHAZ) which is a critical constituent in rating the susceptibility to sensitization in ferritic stainless steel grades; any such information is not available in the literature. Thus, it is imperative to establish the influence of cryogenic cooling on sensitization dynamics in the HTHAZ. This paper discusses the influence of cryogenic cooling on sensitization in an AISI 430 ferritic stainless steel weld. It is established that cryogenic cooling increases the cooling rate in the HTHAZ and reduces the martensite volume percent by an average of 20%. This reduction in martensite content in the HTHAZ increases the level of ditched structure in cryogenically cooled welds and yields more ferrite-martensite ditched grain boundaries than in conventional welds. Although the cryotreated welds exhibit greater ditched boundary, the structure is still classified as nonsensitized, since no single grain boundary is completely surrounded by ditches.